Pelatihan program kekhususan orientasi dan mobilitas pada guru sekolah dasar inklusi di Kota Surabaya - Acep Ovel Novari Beny; Murtadlo Murtadlo; Sri Joeda Andajani (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2023)
The Orientation and Mobility Specialty Program is one of the compensatory services for the visually impaired to be able to carry out their daily activities independently. In inclusive schools, not all classroom teachers or special supervisors fully understand Orientation and Mobility and their practices, so indirectly, the ability of blind students is less than perfect and needs the help of others. The purpose of this training is to improve the Orientation and Mobility of Inclusive Elementary School Teachers and Special Guidance Teachers by using a special training program for the blind, which is carried out for two days with the material presented in the training is mentoring by an alert companion and walking technique using a white cane. The result of this activity is the increasing ability of Orientation and Mobility of Inclusive Elementary School Teachers and Special Guidance Teachers in the City of Surabaya in theory and practice of companion techniques to watch and walk using a white cane which can later be used as a provision in teaching blind students.